The Regret Elements Scale: Distinguishing the emotional and cognitive components of regret - BUCHANAN, Joshua (Institutional Knowledge at Singapore Management University, 2016)
Regret is one of the most common emotions, but researchers generally measure it in an ad-hoc, unvalidated fashion. Three studies outline the construction and validation of the Regret Elements Scale (RES), which distinguishes between an affective component of regret, associated with maladaptive affective outcomes, and a cognitive component of regret, associated with functional preparatory outcomes. The present research demonstrates the RES’s relationship with distress (Study 1), appraisals of emotions (Study 2), and existing measures of regret (Study 3). We further demonstrate the RES’s ability to differentiate regret from other negative emotions (Study 2) and related traits (Study 3). The scale provides both a new theoretical perspective on regret, and a tool for researchers interested in measuring post-decisional regret.